2000
DOI: 10.1210/jcem.85.4.6515
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Cushing’s Syndrome in Patients with Adrenal Incidentaloma: Clinical and Biochemical Features

Abstract: Incidentally discovered adrenal masses are mostly benign, asymptomatic lesions, often arbitrarily considered as nonfunctioning tumors. Recent studies, however, have reported increasing evidence that subtle cortisol production and abnormalities in the hypothalamic-pituitary-adrenal (HPA) axis are more frequent than previously thought. The purpose of this study was to investigate the clinical and hormonal features of patients with incidentally discovered adrenal adenomas, in relation to their clinical outcome. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
296
3
17

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(334 citation statements)
references
References 21 publications
18
296
3
17
Order By: Relevance
“…Other authors have similarly reported the development of overt hypersecretion of the mass over time and even occasional malignant transformation of adrenal incidentalomas (Hensen et al, 1990;Jockenhovel et al, 1992). In contrast, no shift toward malignancy or functional hyperactivity was observed in several other studies (Osella et al, 1994;Barry et al, 1998;Terzolo et al, 1998;Rossi et al, 2000;Siren et al, 2000;Grossrubatscher et al, 2001). Thus, the natural course of adrenal incidentalomas still requires further clarification.…”
Section: Discussionmentioning
confidence: 95%
“…Other authors have similarly reported the development of overt hypersecretion of the mass over time and even occasional malignant transformation of adrenal incidentalomas (Hensen et al, 1990;Jockenhovel et al, 1992). In contrast, no shift toward malignancy or functional hyperactivity was observed in several other studies (Osella et al, 1994;Barry et al, 1998;Terzolo et al, 1998;Rossi et al, 2000;Siren et al, 2000;Grossrubatscher et al, 2001). Thus, the natural course of adrenal incidentalomas still requires further clarification.…”
Section: Discussionmentioning
confidence: 95%
“…There is growing evidence that both stress and glucocorticoids contribute to the etiology of cardiovascular disease; however, the role of glucocorticoids in the stress response has long been a matter of debate (1,3,5,13,15,28,30,31,35,36,38,39,42,48,49,52,58,61,65,67,68,70,71). Recent research has led to the general hypothesis that stress-induced increases in glucocorticoids act in the brain to prepare the organism for future events (12,52).…”
Section: Perspectivesmentioning
confidence: 99%
“…Acute stress rapidly increases blood pressure, heart rate, plasma glucocorticoid concentration, and blood glucose levels (8), while chronic or repeated stress is associated with increases in baseline blood pressure and glucocorticoids (17). Chronically elevated glucocorticoids increase morbidity and mortality from cardiovascular disease and alterations in the glucocorticoid receptor (GR), and in glucocorticoid metabolizing enzymes are associated with hypertension and cardiovascular disease in humans (28,30,35,36,39,48,49,61,65,67,70,71). Thus, chronic stress-induced elevations in glucocorticoids likely contribute to the adverse effects of stress on cardiovascular health.…”
mentioning
confidence: 99%
“…Some authors suggested an association between NFA and mild cortisol overproduction secondary to diseases such as subclinical hypercortisolism or subclinical Cushing syndrome (SCS) (6,7). On the other hand, hyperinsulinemia mediated pathogenesis has been considered by other authors who observed a proliferative effect of insulin on adrenal cancer cells without effect on cortisol synthesis (8).…”
Section: Introductionmentioning
confidence: 99%